Ajuste de estimaciones de densidad ósea en función del tamaño de los huesos - Sánchez Marín, F J; Martínez Celorio, R A; Pérez Luque, E L (Revista Mexicana de Ingenieria Biomedica, 2002)
We show the lack of reliability of the way in which data yielded by densitometers are adjusted, in daily life practice, to estimate Bone Mass Density (BMD). At the same time, we propose a simple alternative that permits better adjustments to measurements of BMD. Errors introduced when BMD is estimated can yield erroneous conclusions with respect to fracture risk, to the effects of certain treatments, to the expression of a given gene, etc. In this study we made use of Digital Radiographic Densitometry and, with data of 63 women, 43 to 60 years old, we show that adjustments of BMD based on the physical dimensions of the calcaneus bone are significantly more reliable that those based on the age, the weight or the height of the patients.